2017
DOI: 10.1088/1361-6560/aa70cc
|View full text |Cite
|
Sign up to set email alerts
|

Subpopulation-based correspondence modelling for improved respiratory motion estimation in the presence of inter-fraction motion variations

Abstract: Correspondence modelling between low-dimensional breathing signals and internal organ motion is a prerequisite for application of advanced techniques in radiotherapy of moving targets. Patient-specific correspondence models can, for example, be built prior to treatment based on a planning 4D CT and simultaneously acquired breathing signals. Reliability of pre-treatment-built models depends, however, on the degree of patient-specific inter-fraction motion variations. This study investigates whether motion estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Incorporating models developed from pre-treatment 4DCBCT [25] rather than a planning 4DCT may also improve the accuracy of the method by compensating for day-to-day changes in patient respiratory motion that may differ from the planning 4DCT model during treatment. Compensating for the changes in internal patient anatomy motion the occurs between the time of planning and the time of treatment could also be done by using subpopulation-based correspondence modeling [96]. Moreover, some techniques have been proposed to model respiratory motion without 4DCT images obtained prior to treatment, which could further reduce the dose delivered to the patient in a clinical context [97,98].…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating models developed from pre-treatment 4DCBCT [25] rather than a planning 4DCT may also improve the accuracy of the method by compensating for day-to-day changes in patient respiratory motion that may differ from the planning 4DCT model during treatment. Compensating for the changes in internal patient anatomy motion the occurs between the time of planning and the time of treatment could also be done by using subpopulation-based correspondence modeling [96]. Moreover, some techniques have been proposed to model respiratory motion without 4DCT images obtained prior to treatment, which could further reduce the dose delivered to the patient in a clinical context [97,98].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical data used in this study were acquired on a GE Lightspeed multislice CT (MSCT) and Discovery combined PET/CT scanners with a cine CT scan capability. These datasets are acquired in a similar fashion as those used in Fayad et al . During data acquisition, the cine 4D CT utilizes the data acquisition modes of 8 × 2.5 mm (2 cm) to produce images of 2.5 mm slice thickness .…”
Section: Methodsmentioning
confidence: 99%
“…In order to resolve this issue, many population models have been previously developed . These models have shown that motion estimation accuracy in the presence of interfraction motion variations can be improved using correspondence models that incorporate motion information from different patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CT, many population models have been previously developed (McQuaid et al 2009, Geimer et al 2017, Fayad, Buerger, Tsoumpas, Cheze-Le-Rest & Visvikis 2012, Wilms et al 2017). These models have shown that motion estimation accuracy in the presence of inter-fraction motion variations can be improved using correspondence models that incorporate motion information from different patients.…”
Section: Population (Atlas-based)mentioning
confidence: 99%